Penggunaan strategi pembelajaran bahasa dalam kalangan pelajar tingkatan dua - Radha Nambiar; Noraini Ibrahim; Pramela Krish (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
According to Chapman (2006), about 20,000 Year Six pupils in schools have been identified as lacking in basic literacy skills. The poor performance of students, which was largely attributed to their being very weak in reading and writing, provided the impetus for a nesting of studies to investigate the reasons for this decline in standards amongst students. This article reports on one study that sets out to investigate the use of language learning strategies among secondary school students in the state of Johor Darul Takzim. A total of 315 students from three rural and urban national type schools participated in a survey and unstructured interviews were held with the students and teachers. Firstly, findings from the study indicate that the poor use of learning strategies could account for their weakness in reading. In addition, only certain strategies which did not require them to be analytical and critical were popular among the students. This article provides suggestions on how to arrest the continuing decline among students by providing them with the necessary strategies to facilitate their learning abilities.